A calculation of periodic data of surface diffeomorphisms with one saddle orbit. - Олена В'ячеславівна Ноздрінова; Ольга Віталіївна Починка (Pracì Mìžnarodnogo Geometričnogo Centru, 2018)
In the paper it is proved that any orientable surface admits an orientation-preserving diffeomorphism with one saddle orbit. It distinguishes in principle the considered class of systems from source-sink diffeomorphisms existing only on the sphere. It is shown that diffeomorphisms with one saddle orbit of a positive type on any surface have exactly three node orbits. In addition, all possible types of periodic data for such diffeomorphisms are established. Namely, formulas are found expressing the periods of the sources through the periods of the sink and the saddle.